Efektivitas Konten Dakwah di Tiktok dalam Meningkatkan Pemahaman Keislaman: Studi Kasus Mahasiswa UIN SMH Banten - Ahmad Aufa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the effectiveness of da'wah content on the TikTok platform in increasing Islamic understanding among students of UIN Sultan Maulana Hasanuddin Banten. The presence of social media has opened up a new space for Islamic da'wah activities, where TikTok with its short and interactive video format has become one of the platforms that is of interest to the younger generation. Using a quantitative approach with a survey method. This study aims to analyze the consumption patterns of da'wah content, attractiveness factors, and their impact on Islamic understanding and practice. Factors that influence the effectiveness of da'wah content on TikTok include attractive visualizations, short duration, use of simple language, and the credibility of the content creator. However, challenges were also found in the form of diverse interpretations and minimal verification of reference sources. This study concludes that TikTok has significant potential as a contemporary da'wah media, especially for the younger generation, with the note that it is necessary to increase Islamic digital literacy to ensure the validity of the information received.